A basic handbook on Information and Communication Technology (ICT) for Art Education - deGraft-Yankson, Patrique (2011)
A thesis submitted to the Department of Art Education, College of Arts and Social Sciences, in partial fulfilment of the requirements for the degree of Master of Arts.